Preparation method and application of high-entropy nano-enzyme with multi-path synergistic antibacterial effect
By synthesizing oxygen-rich vacancies, the problems of single catalytic pathways and poor component tunability of existing nanoenzyme materials are solved, and the multi-path coordinated antibacterial effect is achieved, which significantly improves the killing ability of bacteria and the prevention and control of marine biological pollution.
Patent Information
- Application Number
- CN202411920938.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing anti-fouling nanoenzyme materials have single catalytic pathways and poor component tunability, making it difficult to effectively exert antibacterial effects in complex environments.
The oxygen-rich vacancies with halogen-like peroxidase, peroxidase-like and glutathione-like oxidase-rich high-entropy oxide nanoenzymes with halogen-like peroxidase-like and glutathione-like oxidase-like activities can catalyze the generation of hypobromic acid and hydroxyl radicals, and consume glutathione to achieve multi-path collaborative antibacterial.
Multi-path coordinated and efficient bacterial damage and inactivation have been achieved, which significantly improves antibacterial efficiency, especially in low concentrations to effectively kill high-concentration bacteria, and the bactericidal rate of E. coli and Staphylococcus aureus has reached 100%, and has demonstrated excellent marine biological pollution prevention and control performance.
Smart Images

Figure CN119733526A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanozyme catalytic materials. Specifically, the present invention relates to the preparation of an oxygen vacancy-rich high-entropy oxide with multi-pathway synergistic antibacterial effect as an enzyme-like catalyst for the prevention and treatment of marine biofouling. Background Art
[0002] The generation and development of marine biofouling seriously endangers the sustainable utilization of marine resources and the maintenance of marine ecological balance. Early antifouling materials based on heavy metals can cause marine pollution, death of marine organisms and destruction of ecological balance. Therefore, the development of environmentally friendly marine antifouling materials has become a research hotspot (Li S, Feng K, Li J, et al. Marine antifouling strategies: Emerging opportunities for seawater resource utilization [J]. Chem. Eng. J., 2024, 486, 149859.).
[0003] In recent years, researchers have explored a series of nanomaterials with enzyme catalytic properties, nanozymes, based on the antifouling mechanism of organisms in the marine environment. According to the mechanism of action, they can be divided into nanozymes with reactive oxygen regulation ability, extracellular DNA removal ability and bacterial quorum sensing interference ability (Mei L, Zhu S, Liu Y, et al. An overview of the use of nanozymes in antibacterial applications [J]. Chem. Eng. J. 2021, 418: 129431.). Compared with natural enzymes, nanozymes not only have the advantages of excellent catalytic activity, high stability, and easy large-scale production, but also the unique physical and chemical properties of nanostructures provide more possibilities for the development of new enzyme-based materials (Liang M, Yan X. Nanozymes: From New Concepts, Mechanisms, and Standards to Applications [J]. Acc. Chem. Res. 2019, 52 (8), 2190-2200.).
[0004] However, most of the antifouling nanozymes reported so far exhibit a single catalytic mechanism, and the antibacterial pathway is easily restricted by the actual complex environment and is difficult to function. Patent (CN116554227A) discloses a molybdenum complex nanorod with the ability to produce hypohalous acid. The production of the excellent catalytic performance of the nanorod depends on the catalysis of a higher concentration of H2O2 / bromide ions, which is not conducive to antibacterial and antifouling in the actual environment. Patent (CN116092814A) discloses a Fe2O3@TiO2@MoS2 material with excellent photocatalytic performance and magnetic recyclability. The material only has peroxidase-like activity and has low antibacterial efficiency under non-light conditions. In addition, the relatively single composition also limits the activity regulation of nanozymes.
[0005] High-entropy oxides (HEO) are multi-component metal materials with high configurational entropy, which are synthesized from five or more metal oxides in equal or nearly equal molar ratios. Its unique elemental adjustability and distribution give HEO four major effects that are different from traditional materials: high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect. These effects promote the formation of extremely high thermal stability, strength, toughness, corrosion resistance, and oxidation resistance of HEO, and have attracted widespread attention in the fields of thermoelectricity, magnetocaloric, superconductivity, and catalysis. HEO powders and coating materials derived from them have also been gradually explored (Hsu WL, Tsai CW, Yeh AC, et al. Clarifying the four core effects of high-entropy materials [J]. Nat. Rev. Chem. 2024, 8 (6), 471-485; Aamlid SS, Oudah M, Rottler J, et al. Understanding the Role of Entropy in High Entropy Oxides [J]. J. Am. Chem. Soc 2023, 145 (11), 5991-6006.). However, so far, high-entropy nanozyme catalysts with multi-type enzyme catalytic activity and multi-pathway efficient antifouling prepared based on high-entropy oxides have not been reported.
[0006] In view of this, the inventors of the present application intend to provide a high-entropy nanozyme with multi-pathway synergistic antibacterial effect and a preparation method and use thereof. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art, and further provide a high-entropy nanozyme with multi-pathway synergistic antibacterial effect, a preparation method and use thereof. The high-entropy nanozyme exhibits three types of enzyme activities, namely, haloperoxidase-like, peroxidase-like and glutathione oxidase-like. It can catalyze bromide ions and hydrogen peroxide to generate hypobromous acid with bacterial quorum sensing interference effect and hydroxyl free radicals with structural function destruction effect, and consume glutathione with the function of maintaining the internal redox balance of bacteria, and is used for the prevention and treatment of marine biofouling.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] The preparation method of high entropy nanozyme with multi-pathway synergistic antibacterial effect comprises at least the following steps:
[0010] (1) dissolving a surfactant in a mixed solution of deionized water and anhydrous ethanol and dispersing the mixture by ultrasonication, then adding tannic acid and formaldehyde solution, and stirring the mixture to obtain tannic acid-formaldehyde oligomers;
[0011] (2) adding equimolar solutions of five soluble metal salts of chromium, manganese, iron, nickel, copper, cobalt or zinc to the tannic acid-formaldehyde oligomer obtained in (1), and subjecting the resulting oligomer to covalent cross-linking via a hydrothermal reaction in a weakly alkaline environment regulated by ammonia water to obtain a metal-tannic acid-formaldehyde polymer precursor.
[0012] (3) After the metal-tannic acid-formaldehyde polymer precursor is dried, it is calcined at 800-1000°C in a nitrogen atmosphere, 300-500°C in an air atmosphere, and 300-500°C in a nitrogen / hydrogen mixed atmosphere to obtain a high entropy oxide nanozyme rich in oxygen vacancies, which is labeled as HEO.
[0013] Preferably, the surfactant in step (1) is one of F127, P123, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, triethylamine, poloxamer or similar surfactants.
[0014] Preferably, the dosage ratio of the surfactant, tannic acid and formaldehyde solution in step (1) is 2g:2g:3.8mL.
[0015] Preferably, the soluble metal salt described in step (2) includes any one of nitrate, chloride or sulfate, and the mass ratio of the soluble metal salt to tannic acid is (0.5-1):2.
[0016] Preferably, the hydrothermal reaction conditions in step (2) are 60-200° C. and the time is 10-25 h.
[0017] Preferably, the calcination time in a nitrogen atmosphere at 800-1000° C. in step (3) is 2-4 h; the calcination time in an air atmosphere at 300-500° C. is 3-5 h; the calcination time in a nitrogen / hydrogen mixed atmosphere at 300-500° C. is 1-3 h, and the ratio of nitrogen / hydrogen is (1-50):100 sccm.
[0018] In addition, the present invention provides an application of a high-entropy nanozyme with multi-pathway synergistic antibacterial effects. The high-entropy nanozyme exhibits haloperoxidase-like, peroxidase-like and glutathione oxidase-like activities and is applied to the prevention and treatment of marine biofouling. The specific antibacterial catalytic principle is as follows:
[0019] Haloperoxidase-like: H2O2+HEO+Br - →HOBr
[0020] Peroxidase-like: H2O2+HEO→·OH
[0021] Glutathione oxidase-like: GSH+HEO→CSSG+2H +
[0022] Among them, haloperoxidase-like enzymes can catalyze the oxidation of Br in the presence of H2O2. - It generates hypohalous acid (HOBr), which causes oxidative halogenation reactions in marine bacterial signal molecules, hindering normal cell-to-cell communication, limiting quorum sensing and thus inhibiting biofilm colonization; peroxidase-like enzymes can catalyze H2O2 to generate hydroxyl radicals (·OH), which can efficiently and quickly destroy bacterial structures such as cell membranes and proteins, inhibit bacterial metabolic activity, and thus kill bacteria; glutathione oxidase-like enzymes can promote the consumption of glutathione (GSH) inside bacteria, causing oxidative stress and blocking internal nutrient supply, thereby coordinating the prevention and control of marine biofouling.
[0023] The beneficial effects of the present invention are:
[0024] The present invention relates to high-entropy oxide particles with multi-enzyme-like activity, which can generate hypobromous acid with bacterial quorum sensing interference effect and hydroxyl free radicals with structure and function destruction effect, and promote the consumption of glutathione for maintaining redox balance inside bacteria to cause oxidative stress, and the anti-fouling application of the particles in marine organisms.
[0025] The present invention uses a hydrothermal method and a high-temperature calcination method for the first time to synthesize an oxygen vacancy-rich high-entropy oxide with haloperoxidase-like, peroxidase-like and glutathione oxidase-like activities, which can catalyze bromide ions and hydrogen peroxide to generate hypobromous acid with bacterial quorum sensing interference and hydroxyl radicals with structural function destruction, and consume glutathione with the function of maintaining the internal redox balance of bacteria, thereby achieving multi-pathway synergistic and efficient bacterial damage and inactivation, which is conducive to solving the problems of the single catalytic pathway and poor component adjustability of existing antifouling nanozyme materials, and realizes the practical expansion application of high-entropy nanozyme coatings, and has potential application prospects in the field of marine biological antifouling.
[0026] The high-entropy nanozyme provided by the present invention has the advantages of uniform morphology, large specific surface area, and a large number of active sites and defects, which is conducive to solving the problems of single catalytic pathway and low catalytic activity of existing antifouling nanozyme materials; the multi-element composition also provides more possibilities for its activity regulation; the existing coating preparation technology is also easy to realize the practical expansion application of high-entropy nanozyme coating. It shows three kinds of enzyme activities such as haloperoxidase, peroxidase and glutathione oxidase, which can catalyze bromide ions and hydrogen peroxide to generate hypobromous acid with bacterial quorum sensing interference and hydroxyl radicals with structural function destruction, and consume glutathione with the function of maintaining the internal redox balance of bacteria, which is conducive to multi-pathway efficient sterilization; the antibacterial results show that it exhibits efficient and rapid bactericidal performance, and can effectively catalyze bromide ions and hydrogen peroxide at a low concentration of 0.1 mg / mL, achieving high concentration bacteria (1×10 6 CFU / mL), and the sterilization rates of Escherichia coli and Staphylococcus aureus reached 100%; the results of simulated environmental marine antifouling performance showed that the surface of the plate coated with high-entropy nanozymes had a higher proportion of dead bacteria and less coverage area, and had excellent antibacterial and anti-bacterial adhesion effects. Therefore, high-entropy oxide nanozyme particles rich in oxygen vacancies and with multi-enzyme-like activity showed excellent ability to prevent and treat marine biofouling, and had obvious advantages and prospects for practical application in the field of preparing marine biofouling antifouling materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscopy image of the surface morphology of the high entropy nanozyme prepared in Example 1;
[0028] Figure 2 This is the surface element analysis diagram of the high entropy nanozyme prepared in Example 1;
[0029] Figure 3 This is the X-ray diffraction (XRD) pattern of the high entropy nanozyme prepared in Example 1;
[0030] Figure 4This is a graph showing the experimental results of verifying the oxygen vacancy content of the high entropy nanozyme prepared in Example 1;
[0031] Figure 5 This is a graph showing the experimental results of verifying the haloperoxidase-like catalytic activity of the high entropy nanozyme prepared in Example 1;
[0032] Figure 6 This is a graph showing the experimental results of verifying the peroxidase-like catalytic activity of the high-entropy nanozyme prepared in Example 1;
[0033] Figure 7 This is a diagram showing the experimental results of verifying the glutathione oxidase-like catalytic activity of the high entropy nanozyme prepared in Example 1;
[0034] Figure 8 This is a diagram showing the experimental results of the catalytic production of hypobromous acid by the high entropy nanozyme prepared in Example 1;
[0035] Fig. 9 This is a diagram showing the experimental results of verifying the generation of hydroxyl radicals catalyzed by the high entropy nanozyme prepared in Example 1;
[0036] Fig.10 This is a graph showing the antibacterial performance verification experiment results of the high entropy nanozyme prepared in Example 1;
[0037] Fig.11 This is a graph showing the results of a biological antifouling verification experiment in a simulated marine environment of the high-entropy nanozyme prepared in Example 1. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method is given, but the protection scope of the present invention is not limited to the following embodiments. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention. Unless otherwise specified, the raw materials and reagents in the examples are not specially treated, purchased from commercial channels and used directly; all characterization equipment uses the instrument parameters recommended by the manufacturer.
[0039] Embodiment 1:
[0040] Preparation method of high entropy nanozyme with multi-pathway synergistic antibacterial effect:
[0041] Firstly, 2g F127 was dissolved in a mixed solution of deionized water and anhydrous ethanol and ultrasonically dispersed, 2g tannic acid and 3.8mL formaldehyde solution were added, and the mixture was stirred evenly to obtain tannic acid-formaldehyde oligomers; then, equimolar (1mmol) solutions of five soluble metal nitrates of chromium, manganese, iron, nickel and copper were added to the solution containing tannic acid-formaldehyde oligomers, and the metal-tannic acid-formaldehyde polymer precursor was prepared by covalent cross-linking at 70°C for 15h in a weakly alkaline environment regulated by ammonia water; finally, the polymer precursor was dried and calcined at 900°C in a nitrogen atmosphere (3h), 400°C in an air atmosphere (4h) and 400°C in a nitrogen / hydrogen mixed atmosphere (2h) to obtain a high entropy oxide nanozyme rich in oxygen vacancies, labeled as HEO.
[0042] Embodiment 2:
[0043] Preparation method of high entropy nanozyme with multi-pathway synergistic antibacterial effect:
[0044] Firstly, 2g of P123 was dissolved in a mixed solution of deionized water and anhydrous ethanol and ultrasonically dispersed, and 2g of tannic acid and 3.8mL of formaldehyde solution were added and stirred evenly to obtain tannic acid-formaldehyde oligomers; then, equimolar (0.5mmol) solutions of five soluble metal nitrates of manganese, iron, nickel, copper and zinc were added to the solution containing tannic acid-formaldehyde oligomers, and covalent cross-linking was carried out at 100℃ for 12h in a weakly alkaline environment adjusted by ammonia water to obtain a metal-tannic acid-formaldehyde polymer precursor; finally, the polymer precursor was dried and calcined at 800℃ in a nitrogen atmosphere (3h), 400℃ in an air atmosphere (4h) and 400℃ in a nitrogen / hydrogen mixed atmosphere (2h) to obtain a high-entropy oxide nanozyme rich in oxygen vacancies.
[0045] Embodiment 3:
[0046] Preparation method of high entropy nanozyme with multi-pathway synergistic antibacterial effect:
[0047] Firstly, 2 g of hexadecyltrimethylammonium bromide was dissolved in a mixed solution of deionized water and anhydrous ethanol and ultrasonically dispersed, 2 g of tannic acid and 3.8 mL of formaldehyde solution were added, and the mixture was stirred evenly to obtain tannic acid-formaldehyde oligomers; subsequently, equimolar solutions of five soluble metal nitrates of manganese, iron, nickel, copper and cobalt were added to the solution containing tannic acid-formaldehyde oligomers, and covalent cross-linking was carried out at 150 °C for 20 h in a weakly alkaline environment regulated by ammonia water to obtain a metal-tannic acid-formaldehyde polymer precursor; finally, the polymer precursor was dried and calcined at high temperatures at 1000 °C in a nitrogen atmosphere (4 h), 500 °C in an air atmosphere (5 h) and 500 °C in a nitrogen / hydrogen mixed atmosphere (3 h) to obtain a high-entropy oxide nanozyme rich in oxygen vacancies.
[0048] Through verification experiments, the test results of the enzyme-like activity test, antibacterial performance test and marine biofouling prevention and control performance test of Examples 2 to 3 are consistent with the results of Example 1.
[0049] In Example 1, the surface morphology and surface element analysis of the prepared HEO were analyzed using a FEIQuanta 200 scanning electron microscope with an energy spectrum. Figure 1 and Figure 2 As shown, uniform morphology distribution (average particle size 34.88±8.35 nm) and the presence of Cr, Mn, Fe, Ni, and Cu elements are displayed, which facilitates further preparation of uniform antifouling coating materials as coatings.
[0050] In Example 1, the phase characteristics of the prepared HEO were analyzed using Shimadzu LabX-XRD-6000. Figure 3 As shown, multiple obvious diffraction peaks are displayed, which are attributed to the Fd-3m spinel structure, indicating that the material has a polycrystalline structure and good crystallinity.
[0051] In Example 1, the oxygen vacancy content of the prepared HEO was analyzed by electron paramagnetic resonance technology. Figure 4 As shown, a strong and sharp signal peak is displayed, and its G value is 2.003, indicating that a large number of oxygen vacancies exist, which is beneficial to the improvement of catalytic performance.
[0052] In Example 1, the multi-enzyme activity and catalytic performance of the prepared HEO were analyzed using a Cary 60 UV-visible absorption spectrometer and an LS55 microplate reader:
[0053] ① Test of catalytic activity of haloperoxidase: 100 μg / mL HEO aqueous solution, 100 μmol / L H2O2 and 1 mmol / L Br - Mix well, use 50μmol / L phenol red as the color developer, react at room temperature for 30 minutes, and scan the absorption spectrum curve. Figure 5 As shown, compared with the control group, the ultraviolet absorbance of the reaction solution at 430nm (the absorption peak of phenol red) decreased significantly, while the absorption peak at 589nm (the absorption peak of bromophenol blue generated by bromination of phenol red) increased significantly, confirming the excellent haloperoxidase activity of HEO.
[0054] ② Peroxidase catalytic activity test: Add 100μg / mL HEO aqueous solution, 350μmol / L H2O2 and 0.1mmol / L TMB to acetic acid-sodium acetate buffer solution with a pH of 4.0, react for ten minutes at room temperature, and scan the absorption spectrum curve. Figure 6As shown, compared with the control group, the ultraviolet absorbance of the reaction solution at 652 nm (the absorption peak of ox-TMB generated by TMB oxidation) increased significantly, confirming the excellent peroxidase-like activity of HEO.
[0055] ③ Glutathione oxidase catalytic activity test: 100 μg / mL HEO aqueous solution and 4 mmol / L glutathione (GSH) were mixed evenly and reacted at room temperature for ten minutes. Then 100 μL of the mixture solution was added to a solution containing 0.1 mmol / L TNB and the absorption spectrum curve was scanned. Figure 7 As shown, compared with the control group, the ultraviolet absorbance of the reaction solution at 412 nm (the absorption peak of TNB generated by the DTNB reaction) was significantly reduced, confirming the excellent glutathione oxidase-like activity of HEO.
[0056] ④ Catalytic hypobromous acid generation test: 100μg / mL HEO aqueous solution, 100μmol / L H2O2 and 1mmol / L Br - Mix well, use 50μmol / L lapis lazuli blue as the color developer, react at room temperature for 30 minutes, and scan the absorption spectrum curve. Figure 8 As shown, compared with the control group, the ultraviolet absorbance of the reaction solution at 642 nm (absorption peak of lapis lazuli blue) was significantly reduced, confirming that HEO catalyzed the large-scale production of hypobromous acid.
[0057] ⑤ Catalytic hydroxyl radical generation test: 100μg / mL HEO aqueous solution and 1mmol / L terephthalic acid solution were mixed evenly, reacted at room temperature for ten minutes, and the fluorescence spectrum curve was scanned. Fig. 9 As shown, compared with the control group, the fluorescence intensity of the reaction solution at 430 nm (the peak of 2-hydroxyterephthalic acid generated by the reaction of terephthalic acid) increased significantly, confirming that HEO catalyzed the massive generation of hydroxyl radicals.
[0058] In Example 1, the antibacterial properties of the prepared HEO were analyzed by the dilution plate method. Group settings: ①: Control group: 1×10 6 CFU / mL bacterial solution was added to a 24-well plate and mixed evenly, and then placed in a 37°C incubator for 4 hours; ②: Control+H2O2+Br - Group: 1×10 6 CFU / mL bacterial solution, 100μmol / L H2O2 and 1mmol / L Br - The solution was added to a 24-well plate and mixed evenly, and then placed in a 37°C incubator for 4 h; ③: HEO group: 100 μg / mL HEO solution and 1×10 6CFU / mL bacterial solution was added to a 24-well plate and mixed evenly, and then placed in a 37°C incubator for 4 hours; ④: HEO+H2O2+Br - Group: 100 μg / mL HEO solution, 1×10 6 CFU / mL bacterial solution, 100μmol / L H2O2 and 1mmol / L Br - The solution was added to a 24-well plate and mixed evenly, and then placed in a 37°C incubator for 4 hours. The mixed solution was then diluted and spread on a plate, inverted and placed in a 37°C constant temperature shaker for overnight incubation, and finally the colonies were counted and the antibacterial rate was calculated. Fig.10 As shown in the figure, compared with the control group, the HEO group can effectively kill high-concentration bacteria at a lower concentration, while HEO+H2O2+Br - The sterilization rate of the group against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus) reached 100%;
[0059] In Example 1, the marine biofouling prevention performance of the prepared HEO was analyzed as follows: 0.1 g of HEO powder was mixed with 0.9 g of commercial marine paint and coated on a polypropylene plastic plate, which was then hung in an actual seawater environment for 7 days ( Fig.11 a) Use SYTO 9 and PI dyes to stain the plates for live / dead bacteria and observe. Fig.11 As shown in (b), compared with the blank plate without coating and the control plate coated with coating only, the substrate coated with HEO coating showed more obvious red fluorescence (dead bacteria) and less fouling coverage area, which fully confirmed that HEO has excellent anti-biological fouling ability.
[0060] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect, characterized in that: The specific steps include: Step 1, dissolving a surfactant in a mixed solution of deionized water and anhydrous ethanol and dispersing the mixture by ultrasonication, then adding tannic acid and formaldehyde solution, and stirring to obtain tannic acid-formaldehyde oligomers; Step 2: adding equimolar solutions of at least five soluble metal salts of chromium, manganese, iron, nickel, copper, cobalt or zinc to the tannic acid-formaldehyde oligomer obtained in step 1, and subjecting the resulting oligomer to covalent cross-linking via hydrothermal reaction in a weakly alkaline environment regulated by ammonia water to obtain a metal-tannic acid-formaldehyde polymer precursor; Step 3: After drying the metal-tannic acid-formaldehyde polymer precursor, it is calcined in a nitrogen atmosphere at 800-1000°C, an air atmosphere at 300-500°C, and a nitrogen / hydrogen mixed atmosphere at 300-500°C to obtain a high-entropy oxide nanozyme rich in oxygen vacancies, which is labeled as HEO.
2. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to claim 1, characterized in that: In the step 1, the surfactant is one of F127, P123, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, triethylamine, poloxamer or similar surfactants.
3. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to claim 1, characterized in that: In the step 1, the dosage ratio of the surfactant, tannic acid and formaldehyde solution is 2g:2g:3.8mL.
4. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to claim 1, characterized in that: The soluble metal salt in step 2 includes any one of nitrate, chloride or sulfate, and the mass ratio of the soluble metal salt to tannic acid is (0.5-1):
2.
5. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to claim 1, characterized in that: The hydrothermal reaction conditions in step 2 are 60° C. to 200° C. and the reaction time is 10 to 25 hours.
6. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to claim 1, characterized in that: In the step three, the calcination time of the metal-tannic acid-formaldehyde polymer precursor in a nitrogen atmosphere at 800-1000° C. is 2-4 hours; the calcination time in an air atmosphere at 300-500° C. is 3-5 hours; the calcination time in a nitrogen / hydrogen atmosphere at 300-500° C. is 1-3 hours, and the ratio of nitrogen / hydrogen is (1-50):100sccm.
7. The method for preparing a high-entropy nanozyme with multi-pathway synergistic antibacterial effect according to any one of claims 1 to 6, characterized in that: The obtained HEO sample has a single crystal phase of Fd-3m spinel structure with a particle size of 34.88±8.35nm.
8. The use of a high entropy nanozyme with multi-pathway synergistic antibacterial effect according to any one of claims 1 to 6, characterized in that: The high-entropy nanozyme exhibits haloperoxidase-like, peroxidase-like and glutathione oxidase-like activities, and can catalyze bromide ions and hydrogen peroxide to generate hypobromous acid that interferes with bacterial quorum sensing and hydroxyl radicals that destroy structure and function, and consume glutathione that maintains the internal redox balance of bacteria, and is used for the prevention and treatment of marine biofouling.
Citation Information
Patent Citations
Preparation method of recovery type Fe2O3-coated TiO2-coated MoS2 nano bacteriostatic magnetic material
CN116092814A
Molybdenum complex nanorod as well as preparation method and marine anti-fouling application thereof
CN116554227A
Spinel type mesoporous high-entropy oxide nanosphere with hollow structure, preparation method and application thereof
CN111333124A
Preparation method of foamed nickel-loaded amorphous phosphorus-doped nickel molybdate bifunctional electrocatalytic electrode and application thereof
CN111663152A
Application of spherical mesoporous high-entropy metal catalyst in carbon dioxide hydrogenation catalysis
CN117753199A
Cited By
High-entropy oxide material rich in oxygen vacancies as well as preparation method and application of high-entropy oxide material
CN122233450A
High-entropy oxide material rich in oxygen vacancies and preparation method and application thereof
CN122233450B